2021
DOI: 10.3389/fphys.2021.779683
|View full text |Cite
|
Sign up to set email alerts
|

In situ Metabolomics of Metabolic Reprogramming Involved in a Mouse Model of Type 2 Diabetic Kidney Disease

Abstract: The in situ metabolic profiling of the kidney is crucial to investigate the complex metabolic reprogramming underlying diabetic kidney disease (DKD) and to allow exploration of potential metabolic targets to improve kidney function. However, as the kidney is a highly heterogeneous organ, traditional metabolomic methods based on bulk analysis that produce an averaged measurement are inadequate. Herein, we employed an in situ metabolomics approach to discover alternations of DKD-associated metabolites and metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…Although there have been few publications discussing a direct association between unsaturated fatty acids and DKD, low linolenic and linoleic acid intake are associated with CKD in T2DM patients, suggesting an insufficiency of glycerol phospholipid in DKD patients [ 46 ]. In our study, KEGG pathway analysis showed that the unsaturated fatty acids biosynthesis pathway was significantly affected, similar to the metabolic reprogramming observed in a mouse model of DKD [ 26 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although there have been few publications discussing a direct association between unsaturated fatty acids and DKD, low linolenic and linoleic acid intake are associated with CKD in T2DM patients, suggesting an insufficiency of glycerol phospholipid in DKD patients [ 46 ]. In our study, KEGG pathway analysis showed that the unsaturated fatty acids biosynthesis pathway was significantly affected, similar to the metabolic reprogramming observed in a mouse model of DKD [ 26 ].…”
Section: Discussionsupporting
confidence: 77%
“…In a mouse model of DKD, Bai Linnan et al. used situ metabolomics to show perturbation in arginine and proline metabolism [ 26 ]. An earlier study showed that plasma levels of amino acids such as proline, ornithine, and citrulline, were significantly elevated in uremic patients before dialysis, compared with controls, indicating abnormalities in amino acid metabolism, especially proline metabolism [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fan charts ( Figure 4 C,D) depict the proportion of differential metabolites found in the different regions of the kidney. The analysis revealed that the ranking of the number of discriminating metabolites identified in the different regions of the HFD/STZ-induced rat kidneys was OM/C > W > IM, while in the db/db mice, the ranking was OM > W > C > IM, indicating that the outer medulla region may be more vulnerable to diabetic renal damage in comparison to the other regions [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the importance is evident to investigate molecular changes in nephron segments besides the glomerulus. Others have applied MALDI-MSI to investigate molecular changes of the kidney in animal models of early diabetes and DN [13][14][15][16][17][18] . These studies all revealed changes in renal metabolism upon diabetes, with differences in response between the cortical and medullary regions.…”
Section: Openmentioning
confidence: 99%